Discordance between ABC blood phenotype and genotype in a domestic short‐haired cat - Argyrios Ginoudis; Bertrand Canard; Alexandra Kehl; Urs Giger; Christos Koutinas; Stella Christoforaki; Erasmia Smyroglou; Zoe Polizopoulou; Mathios E. Mylonakis (Journal of Veterinary Internal Medicine, 2024)
Abstract An adult domestic short‐haired feline leukemia virus‐infected cat was referred for kidney failure and worsening anemia requiring transfusions. ABC blood typing was performed with an immunochromatographic strip assay at different occasions. Gel column systems were used for the major and minor crossmatching tests, and anti‐A and anti‐B titers were determined. No discrete A or B bands appeared on the immunochromatographic strips at any time point for the recipient cat. The recipient's plasma agglutinated RBCs from tested type A and B cats. The recipient's RBCs appeared compatible with plasma from 1 type A and 2 B donors, and incompatible with plasma from another type A cat. Genotyping of recipient blood revealed a single homozygous c.179G>T CMAH variant predicting a blood type B. These studies suggest an unusual weak type B or missing all ABC antigens. The latter resembles the exceedingly rare Bombay phenotype in the human ABO blood group system.